A simple mesh-update procedure for fluid–structure interaction problems. (June 2016) - Jendoubi, A.; Deteix, J.; Fortin, A.
Highlights: New mesh-update for FSI problems. Parabolic extension. Large displacements. Mesh quality. Abstract: Knowing the displacements of the solid boundary, various techniques have been proposed to update the fluid mesh in fluid–structure interaction problems. The ideal moving mesh method must be cheap, avoid the generation of degenerated elements and provide good quality elements to ease the finite element solution. We therefore introduce a very simple moving mesh method allowing for very large deformation in static problems and to very large time steps for time-dependent problems. We compare our method with more classical approaches such as harmonic extension and radial basis function method through a number of test problems and we analyze their performances.